ANALISIS NILAI RELIGIUS PADA BUKU LAPIS-LAPIS KEBERKAHAN KARYA SALIM AFILLAH - Lara Arum Sari; Mardeli Mardeli; Ermis Suryana (PAI RAFAH, 2022)
Religious values are values that regulate religious or religious life, a bond or relationship between humans and their God. Religious values have a relationship with worldly life, not much different from other values such as culture and social aspects. a mysterious afterlife for life. It is this afterlife that distinguishes it from other values. Religious value is also an obedient attitude or behavior in carrying out Islamic religious teachings that always worship because the task of humans as servants of Allah is to serve Him. The type of research used in this research is library research. Literature research is research that uses reading materials as a reference source. It means collecting data by reading, studying, understanding, and analyzing documents related to the research. The data collection technique used is documentation. While the data analysis method used is using content analysis. The results of the study stated that the religious values in the Lapis-Lapis Blessing book have three aspects of life, namely the value of aqidah, the value of worship, and the value of morals. The value of aqidah includes several things, namely faith in Allah SWT, belief in Allah's provisions and faith in apostles. The value of worship includes several things, namely; prayer, dhikr, prayer, and reading of the Qur'an. While the moral values include several things, namely; patient, please help, entertain guests, trust, and giving charity. The implementation of these three aspects requires assistance from parents, schools, and the community so that children can have their religious values embedded from a young age. So the need for deep appreciation when teaching children several things about religious values, one of which is the value of aqidah, worship, and morals.